Jorge Amado: um cronista da guerra - Muraca, Márcio Henrique (2012)
The present study investigates Jorge Amado s 103 articles compiled in the book Hora da Guerra (2008) published between 1942 and 1945 on the newspaper O Imparcial (city of Salvador, Bahia state). As a methodological principle, a bibliographical review based on the author s life and work, especially in the period of Estado Novo (1937-1945), books on newspaper articles and journalism, on Second World War, as well as references on themes that were focused in this analysis: censorship, anti-semitism and the Nazi leader Adolf Hitler. In light of such issues, the study searched for the relationship between literature and history, newspaper article and political engagement, by verifying mostly the decision made by the Communist Party at the War time and how they influenced the author s writing. Communist ideology that is clearly seen in the texts was put in face with Jorge Amado s humanist position, which sometimes revealed contradictions or antagonistic signals as a result of the tension between the author s political engagement in the most overwhelming period of the twentieth century and his worldview in favour of the oppressed people. In formal terms, it is also clear in the texts the colloquial language permeated by a pamphlet discourse , sometimes dressed up in an emotional way with a voice of indignation, especially when it comes to victims of Nazi fascism. Newspaper article as literary texts was also questioned based on authors who reflected on such literary genre, on newspaper as a source of income for writers, as well as Jorge Amado s thoughts on journalism. This study was concluded with some reflections that emerged from the intersection between Jorge Amado s literary and ideological project, the validity of his War articles in literary studies and the spirit of a time as well as the many facets of a writer that emerge not by verifying his well-known work, but by focusing on those unknown to both literary critics and general readers.